2007
DOI: 10.1113/expphysiol.2007.037481
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor‐mediated inhibition of respiration after peripheral and central administration of a 5‐HT1A receptor agonist in neonatal piglets

Abstract: Inhibition of neurones in the ventral medulla accentuates the respiratory inhibition associated with acute blood pressure elevation in piglets. Activation of presynaptic 5-HT 1A receptors inhibits serotonergic neurones in the ventral medulla and caudal raphé, and we tested the hypothesis that administration of 8-hydroxydipropylaminotetralin (8-OH-DPAT), a 5-HT 1A agonist, within the rostroventral medulla and caudal raphé would enhance baroreceptor-mediated inhibition of respiratory activity in decerebrate, neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Urapidil is known to cross the placenta and, consequently, (side-)effects can be anticipated. This is supported by a recent study of Curran and Leiter showing the impact of the central 5-HT1 agonist on respiratory drive in neonatal piglets [1,6].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Urapidil is known to cross the placenta and, consequently, (side-)effects can be anticipated. This is supported by a recent study of Curran and Leiter showing the impact of the central 5-HT1 agonist on respiratory drive in neonatal piglets [1,6].…”
Section: Introductionsupporting
confidence: 71%
“…Goda et al showed that a bolus intravenous administration of 5-HT immediately produced apnea in rats [2,3]. Curran and Leiter recently reported on the impact of the central 5-HT1 agonist on respiratory drive in neonatal piglets by baroreceptor stimulation [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive animal data indicate that 5-HT influences multiple homeostatic functions mediated by the medulla, including: (1) central chemoreception to carbon dioxide and/or oxygen (Bradley et al, 2002;Nattie, Li, Richerson, & Lappi, 2004;Taylor, Li, Green, Kinney, & Nattie, 2004;Wang, Tiwari, Bradley, Zaykin, & Richerson, 2001); (2) medullary respiratory rhythm generation during development (Bou-Flores et al, 2000); (3) maturation of the medullary and phrenic respiratory network in prenatal development (Bou-Flores et al, 2000); (4) cardiovascular function (Curran & Leiter, 2007;Pelaez, Schreihofer, & Guyenet, 2002); (5) thermoregulation Nagai, 1992;Ootsuka & Blessing, 2006); (6) upper airway control (Gao & Mason, 2001;Hilaire, Morin, Lajard, & Monteau, 1993;Monteau, Morin, Hennequin, & Hilaire, 1990); (7) respiratory rhythm generation (Gunther, Maroteaux, & Schwarzacher, 2006;Pena & Ramirez, 2002), and (8) sleep/waking cycles (Brown, Sirlin, Benoit, Hoffman, & Darnall, 2007). A distinct feature of 5-HT neurons is that they exhibit differential firing rates according to the level of arousal, with increased firing during waking, decreased firing during NREM, and almost complete absence of firing during REM (McGinty & Harper, 1976;Trulson & Jacobs, 1979).…”
Section: Serotonin and Brainstem Mechanisms In Sidsmentioning
confidence: 99%
“…During hypercapnia, CO 2 increases mean arterial blood pressure by a direct effect on vessels and by sympathetic activation (13,23,32). This increase in blood pressure activates baroreceptors that modulate respiratory activity and decreases breathing frequency (9,25). Therefore, the baroreflex potentiation is another mechanism by which NMS could attenuate the HCVR.…”
mentioning
confidence: 99%